2012
DOI: 10.1371/journal.pone.0031086
|View full text |Cite
|
Sign up to set email alerts
|

Association between OLR1 K167N SNP and Intima Media Thickness of the Common Carotid Artery in the General Population

Abstract: Background and PurposeThe lectin-like oxidised LDL receptor-1 (OLR1) gene encodes a scavenger receptor implicated in the pathogenesis of atherosclerosis. Although functional roles have been suggested for two variants, epidemiological studies on OLR1 have been inconsistent. Methods - We tested the association between the non-synonymous substitution K167N (rs11053646) and intima media thickness of the common carotid artery (CCA-IMT) in 2,141 samples from the Progression of Lesions in the Intima of the Carotid (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Among them, ultrasound detection and quantification of the common carotid artery wall thickness (intima-media thickness, IMT) are considered a surrogate marker of subclinical atherosclerosis [93, 94]. The association between the nonsynonymous substitution K167N (rs11053646) and IMT has been tested in 2,141 samples from the Progression of Lesions in the Intima of the Carotid (PLIC) study (a prospective population-based study) [95]. Significantly increased IMT has been observed in male carriers of the minor C (N) allele compared to GC and GG (KN and KK) genotypes [95].…”
Section: Genetics Of Lox-1 and Atherosclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, ultrasound detection and quantification of the common carotid artery wall thickness (intima-media thickness, IMT) are considered a surrogate marker of subclinical atherosclerosis [93, 94]. The association between the nonsynonymous substitution K167N (rs11053646) and IMT has been tested in 2,141 samples from the Progression of Lesions in the Intima of the Carotid (PLIC) study (a prospective population-based study) [95]. Significantly increased IMT has been observed in male carriers of the minor C (N) allele compared to GC and GG (KN and KK) genotypes [95].…”
Section: Genetics Of Lox-1 and Atherosclerosismentioning
confidence: 99%
“…The association between the nonsynonymous substitution K167N (rs11053646) and IMT has been tested in 2,141 samples from the Progression of Lesions in the Intima of the Carotid (PLIC) study (a prospective population-based study) [95]. Significantly increased IMT has been observed in male carriers of the minor C (N) allele compared to GC and GG (KN and KK) genotypes [95]. A gender-specific association has been also described between the C (N) allele and prevalence of carotid plaque also in a cohort of Dominican-Hispanic origin [96].…”
Section: Genetics Of Lox-1 and Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…Carotid IMT, as measured by highresolution ultrasound, is a widely used marker of subclinical atherosclerosis. Previous studies have shown associations of genotype and IMT (40), and increased IMT has been associated with increased risk of MI and stroke (4,40,41). In the present study, we chose to use this established measurement of subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%